Exploring the Social-Political Nexus in Islam: A Comparison of the Middle East and Southeast Asia - Fealy, Greg (Muslim Politics Review, 2022)
One of the fulcrums of change in political Islam is the relationship between traditional patterns of Islamic politics, which focus upon the pursuit and wielding of formal power, particularly with the aim of enacting of shari’a law, and the more recent emergence of dynamic social spheres of Islamic activism, which emphasise values and moral order and operate with considerable autonomy from Islamic parties. This article explores the nature of the interactions between political and social activism and identifies the ways in which more established form of political Islam are changing as a result of pressure from the social realm.  It compares case studies from the Middle East and Southeast Asia, paying particular attention to Muslim Brotherhood and Salafist expressions of social and political activism in both regions.  It argues that burgeoning pietistic social activism presents both challenges and opportunities to Islamic political actors, and that failure to engage with these new forces will lead to further marginalisation and the risk of declining relevance.